Experimental characterisation of as-built and retrofitted timber-masonry connections under monotonic, cyclic and dynamic loading. (5th December 2022) - Mirra, Michele; Ravenshorst, Geert; de Vries, Peter; Messali, Francesco
Highlights: Testing as-built and strengthened timber-masonry connections. Analysis of monotonic, cyclic and dynamic behavior of timber-masonry joints. Masonry subjected to induced earthquakes may undergo less damage than in quasi-static tests. Abstract: In the province of Groningen (NL), where human-induced earthquakes take place due to gas extraction, a large part of the building stock is composed of brick masonry walls and timber diaphragms. In this framework, timber-masonry connections play a crucial role in the global seismic response of the buildings, but their properties and structural behaviour have not been investigated yet for the Dutch context. This work describes the experimental campaign conducted at Delft University of Technology to characterize as-built and strengthened timber-masonry connections. The joints were tested under either quasi-static monotonic, cyclic or dynamic loading, to analyse the effect of an induced earthquake signal on the connections' response in terms of strength, stiffness and damage evolution. The obtained test results provided more insight into the capacity and properties of existing connections, and useful knowledge on the effectiveness of the tested retrofitting methods.